2019
DOI: 10.18502/jpc.v7i1-2.1620
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Foods for Skin Health

Abstract: Various medicinally uses of the natural foods as well as edibility of them caused attraction a huge attention for several pharmacological activities include antioxidants, antibiotics and antineoplastic activity. Aging is a major risk factor in the change of convert skin structure and function might also directly affect skin appearance. Age-related disorders in the skin health are a consequence of the accumulation of cellular damage and reduced activity of protective stress response pathways leading to low-grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License (oxygen and nitrogen species) that induce OS (Lu and Yeap, 2000;Pousset, 2006;Varban et al, 2009;Akalin and Selamoglu., 2019). In the present study, Bauhinia monandra of the botanical Fabaceae family was the focus of our investigations through an ethnobotanical survey that we conducted in Côte d'Ivoire.…”
Section: Introductionmentioning
confidence: 93%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License (oxygen and nitrogen species) that induce OS (Lu and Yeap, 2000;Pousset, 2006;Varban et al, 2009;Akalin and Selamoglu., 2019). In the present study, Bauhinia monandra of the botanical Fabaceae family was the focus of our investigations through an ethnobotanical survey that we conducted in Côte d'Ivoire.…”
Section: Introductionmentioning
confidence: 93%
“…This can also enhance the nutritional value of foods. As these antioxidants continue to be used in food preservation, they may contribute to the development of new ways to use natural antioxidants instead of synthetics [25][26][27][28][29].…”
Section: Biological Activities Of Lycopenementioning
confidence: 99%
“…The fact that foods of natural origin are both medicinal and edible, contain antioxidants, antibiotics and structures that provide antineoplastic effects, have also become a subject of interest for many pharmacological activity studies (Sevindik et.al., 2017). As a result of the studies carried out; It has been found out that the consumption of various phenolic compounds found in natural foods can reduce the possibility of significant health problems in people due to their antioxidant effects as well as many mechanisms (Akalın and Selamoğlu, 2019;Sevindik et al, 2017;Pehlivan et al, 2021). Among the most common product types in studies on products containing aronia; teas, yoghurts, nectars, juices, jellies, chewing gums, concentrated juices and chewable tablets (Engels and Brinkman, 2014).…”
Section: Introductionmentioning
confidence: 99%